Current Press Management and Marketing: Global Experience and Issues of Domestic Publications (Herald of Journalism, 2025)
As technology advances, the competition for information has intensified. Especially for periodicals, failing to keep up with new trends makes it difficult to retain readers’ attention. This study aims to analyze management and marketing systems in periodical press, compare global practices, and identify key issues in domestic publications. The research hypothesis suggests that implementing effective media management and digital marketing strategies enhances the competitiveness of periodicals. The relevance of the study is linked to the growing competition in the information space and the need for press adaptation to new media requirements. The research methodology includes comparative analysis, descriptive research, SWOT analysis, and statistical methods. The management and marketing strategies of domestic and foreign periodicals were compared, and ways to improve their efficiency were proposed. The findings indicate that the domestic press needs to develop digital platforms, effectively utilize social media, and strengthen reader engagement. These recommendations contribute to the sustainable development of publications in the market, audience expansion, and financial stability.
Keywords: media, management, marketing, digital media, audience, media strategy.